Tesla [videorecording (DVD)] - Almereyda, Michael; Hawke, Ethan, 1970-; Hewson, Eve; Keshawarz, Donnie; Hamilton, Josh; Moss-Bachrach, Ebon; Gaffigan, Jim; MacLachlan, Kyle, 1959- (Shout! Factory, 2021)
Brilliant, visionary Nikola Tesla fights an uphill battle to bring his revolutionary electrical system to fruition, then faces thornier challenges with his new system for worldwide wireless energy. The film tracks Tesla's uneasy interactions with his fellow inventor Thomas Edison and his patron George Westinghouse. Another thread traces Tesla's sidewinding courtship of financial titan J.P. Morgan, whose daughter Anne takes a more than casual interest in the inventor.